A sigmoidal equation for the high strain rate compression of porous metals. (March 2020) - Ruestes, Carlos J.; Bertolino, Graciela M.; Ruda, Margarita; Bringa, Eduardo M.
Highlights: We present a simple sigmoidal equation able to fit the compaction behavior ( α - epsilon) of - epsilon) of porous metals under high strain rate compression. The equation requires only 4 input parameters. Each of these parameters has a physical meaning. Parameters can be determined by non linear regression analysis of simulations or experimental data. Good agreement is found compared to molecular dynamics simulations of nano-scale porosity, as well as to data of dynamic collapse of micro-scale porosity available in the literature. The equation can be used in macro-scale codes where nano-scale porosity cannot be modeled explicitly. Abstract: The high strain rate compression of porous materials is a problem that presents a series of difficulties to continuum-scale codes, its computational cost being a major one. Following previous contributions suggesting that compaction can be defined in terms of volumetric strain, we propose to model the compaction of porous metals by means of a sigmoidal equation. The definition requires only four parameters, each of them with a physical meaning. We tested the proposed equation against molecular dynamics simulations of high strain rate compression of closed-cell and open-cell foams, as well as micro-scale data available in the literature. The equation can be used in micro and macro-scale codes where nano-scale porosity cannot be modeled explicitly.